Operations Research Problems Statements and Solutions - Poler, Raúl.; Mula, Josefa; Díaz-Madroñero, Manuel; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
The objective of this book is to provide a valuable compendium of problems as a reference for undergraduate and graduate students, faculty, researchers and practitioners of operations research and management science. These problems can serve as a basis for the development or study of assignments and exams. Also, they can be useful as a guide for the first stage of the model formulation, i.e. the definition of a problem. The book is divided into 11 chapters that address the following topics: Linear programming, integer programming, non linear programming, network modeling, inventory theory, queue theory, tree decision, game theory, dynamic programming and markov processes. Readers are going to find a considerable number of statements of operations research applications for management decision-making. The solutions of these problems are provided in a concise way although all topics start with a more developed resolution. The proposed problems are based on the research experience of the authors in real-world companies so much as on the teaching experience of the authors in order to develop exam problems for industrial engineering and business administration studies.
Linear programming -- Integer programming -- Non-linear programming -- Network Modelling -- Inventory theory -- Queuing theory -- Decision theory -- Game theory -- Dynamic programming -- Markov processes.
Keywords: Industrial engineering; Production engineering; Operations research; Decision making; Game theory; Industrial and Production Engineering; Operations Research/Decision Theory; Game Theory, Economics, Social and Behav. Sciences